The Influence of Organizational Culture and Motivation on Employee Performance - Tarmizi, Achmad; Lian, Bukman; Puspita, Yenny (Journal of Social Work and Science Education, 2021)
This study focuses on the problem of how the influence of organizational culture and motivation on employee performance of the Ogan Komering Ulu district education office. This research was descriptive quantitative, the questionnaire and documentation were used as instruments. The results showed that there was a positive and significant influence between organizational culture and motivation on employee performance partially and simultaneously. It contributes to more concentrate on organizational culture and motivation to improve employee performance.